A Study of Research Values for Private University Faculty - Rattanapian, Janejira; Natakuatoong, Onjaree; Songkram, Naowanit (Scholar: Human Sciences, 2017)
Conducting research is considered another important obligation of both private and public university lecturers apart from teaching. Concerning conducting research, good researchers satisfactorily need to have research values. The objectives of this research were 1) to determine research values needed for private university faculty and 2) to identify research values for private universities across the research process. The samples comprised 15 research lecturers and professional researchers with more than five years of research experience. The interviews as the core research data collection of this study were conducted based on the research values synthesized from published documents and academic journals. The findings of this study revealed that research values for private university faculty include 13 core values categorized under three categories as follows: Category 1 – Creativity Values consisting of three sub-core values: 1) generating new research ideas, 2) daring to face research challenges, and 3) conducting research beneficial to society; Category 2 – Professional Researcher Values consisting of six sub-core values: 4) working systematically, 5) having good human relations, 6) having no prejudice, 7) having high responsibility, 8) thinking logically and 9) not violating human rights; and Category 3 –Adherence to the Truth Values comprising four sub-core values: 10) being competent in searching for information, 11) being truthful to the data observed 12) avoiding committing plagiarism and 13) presenting quality research. It was also found that Creativity Values were most frequently used in the phase of determining research problems. Professional Researcher Values were most frequently used in the phases of designing research methodology, creating research instruments, collecting the data, analyzing the data and discussing and concluding the results of the study. Adherence to the Truth Values were most frequently used in summary, discussion and research presentation phases.